Expediente - Horizonte, Belo Horizonte, v. 18, n. 56, maio.-ago. 2020 - Souza, Carlos Frederico Barbosa de (HORIZONTE - Revista de Estudos de Teologia e Ciências da Religião, 2020)
Expediente - Horizonte, Belo Horizonte, v. 18, n. 56, maio.-ago. 2020